Comprehensive Geriatric Assessment (CGA) based risk factors for increased caregiver burden among elderly Asian patients with cancer. Issue 3 (May 2016) - Rajasekaran, Tanujaa; Tan, Tira; Ong, Whee Sze; Koo, Khai Nee; Chan, Lili; Poon, Donald; Roy Chowdhury, Anupama; Krishna, Lalit; Kanesvaran, Ravindran
Abstract: Objective: This study aims to identify Comprehensive Geriatric Assessment (CGA) based risk factors to help predict caregiver burden among elderly patients with cancer. Materials and Method: The study evaluated 249 patients newly diagnosed with cancer, aged 70 years and above, who attended the geriatric oncology clinic at the National Cancer Centre Singapore between 2007 and 2010. Results: Out of 249 patients, 244 patients had information available on family caregiver burden and were analysed. On univariate analysis, ADL dependence, lower IADL scores, ECOG performance status of 3–4, higher fall risk, lower scores in dominant hand grip strength test and mini mental state examination, polypharmacy, higher nutritional risk, haemoglobin < 12 g/dL and presence of geriatric syndromes were significantly associated with mild to severe caregiver burden. On multivariate analysis, only ECOG performance status of 3–4 (odds ratio [OR], 4.47; 95% confidence interval [CI], 2.27–8.80) and haemoglobin < 12 g/dL (OR, 2.38; 95% CI, 1.14–4.99) were associated with an increased probability of mild to severe caregiver burden. The model achieved a good fit (Hosmer–Lemeshow's p = 0.196) and discrimination (area under the curve [AUC] = 0.742; bias-corrected AUC = 0.737). Based on this, patients were stratified into 3 risk groups with different proportion of patients with increased caregiver burden (low risk: 3.9% vs intermediate risk: 18.8% vs high risk: 39.6%; p < 0.001). Conclusion: ECOG performance status and haemoglobin were associated with increased caregiver burden among elderly patients with cancer. Using these two factors in the clinic may help clinicians identify caregivers at risk and take preventive action to mitigate that.